South Africa : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report, 2018)
Reflecting slow progress on reforms, weakened governance, and elevated policy uncertainty, growth remains subdued. With the economy unable to create enough jobs, the quest for inclusive growth has been elusive, making South Africa one of the most unequal societies. Growing government spending has led to a doubling of public debt in the last decade. Credible monetary policy has kept inflation expectations anchored, albeit at near the top of the target band. The current account deficit remains financed by potentially volatile portfolio inflows. The new administration's immediate priority has focused on improving governance and restoring confidence.